2008
DOI: 10.1080/03014220809510555
|View full text |Cite
|
Sign up to set email alerts
|

A values‐based process for cross‐cultural dialogue between scientists and Māori

Abstract: Cross-cultural dialogue is an essential part of the evaluation of controversial technologies and research proposals of significance to indigenous peoples. If Māori in Aotearoa/New Zealand are to benefit from these technologies it is important that effective processes are developed and implemented to ensure enduring outcomes for their communities. We describe a deliberate, multi-stage process to facilitate cross-cultural dialogue that starts well before research applications are submitted to funding and/or regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…This includes Māori involvement at all levels of the research, Māori setting the research agenda, Māori determining the interpretation and dissemination of research outputs, and Māori involvement in governance of samples and data [4–6, 27–29, 35]. Tribal communities in New Zealand have stressed the importance of their involvement in governance of research and biobanking activities due to the level of risk for participants, the cultural importance of tissue, DNA, data, and the need for collaborative relationships to ensure benefits are realized in their communities [12].…”
Section: Discussionmentioning
confidence: 99%
“…This includes Māori involvement at all levels of the research, Māori setting the research agenda, Māori determining the interpretation and dissemination of research outputs, and Māori involvement in governance of samples and data [4–6, 27–29, 35]. Tribal communities in New Zealand have stressed the importance of their involvement in governance of research and biobanking activities due to the level of risk for participants, the cultural importance of tissue, DNA, data, and the need for collaborative relationships to ensure benefits are realized in their communities [12].…”
Section: Discussionmentioning
confidence: 99%
“…Participants in this study suggested that the effect of gene editing on Māori values is not always in a negative direction and it was suggested that whakapapa, mana, mauri, and kaitiakitanga might be enhanced through the use of gene editing technologies. This suggests that values based frameworks developed for other gene based technologies (Wilcox et al, 2008; Hudson et al, 2016c) will remain relevant in for gene editing applications. What the enhancement or diminishment of these Māori values might look like is summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Ko Aotearoa Tēnei/This is New Zealand , conventionally known as WAI 262, http://www.waitangitribunal.govt.nz/) and various approaches have been developed to facilitate such engagement (Tipene‐Matua & Henaghan ; Wilcox et al . ; Hudson et al . ).…”
Section: Strong Relationships Lead To Mutually Beneficial Genomic Advmentioning
confidence: 97%